Feed intake and Growth Performance of Different Types of Coloured Chickens Reared under Intensive System in Tropical Humid Climate - Rath, J. (Indian Journal of Animal Nutrition, 2021)
The study was carried out to evaluate the feed consumption and performance of five coloured types of chickens reared under intensive system in the hot and humid climate conditions. The growth parameters like body weight, feed consumption, and feed conversion ratio of the coloured birds like Aseel, Dahlem Red, Kaveri, Kadaknath and Rhode Island Red were studied in the intensive conditions. Carcass characteristics, incidence of mortality and cost of production of different types of coloured chicken were measured. Kaveri showed the highest body weight gain and Kadaknath the lowest (P≤0.05) among the five types and the sequence found was: Kaveri>Dahlem Red>RIR>Assel and Kadaknath. Feed conversion ratio followed the order: Kadaknath/RIR/Dahlem Red> Aseel>Kaveri, the differences being significant (P≤0.05). The mortality rate was highest for Rhode Island Red (20%) followed by Dahlem Red (10%), Kaveri/Kadaknath (8%) and Aseel (2%). The dressing percentage was higher in Rhode Island Red, Kaveri and Dalhem Red than Assel and Kadaknath. Some other carcass parameters like back, thigh and drum stick yield percentage also differed significantly among the types of chicken. The cost of production per kg live weight or per kg dressed weight was the lowest for Kaveri and highest for Kadaknath. From the above experiment it was concluded that Kaveri excelled the other colored chicken type in respect to the body weight gain, feed efficiency followed by RIR, Dahlem Red and Aseel.